Assessing Homogeneity and Climate Variability of Temperature and Precipitation Series in the Capitals of North-Eastern Brazil - Hänsel, Stephanie; Medeiros, Deusdedit M.; Matschullat, Jörg; Petta, Reinaldo A.; de Mendonça Silva, Isamara (Frontiers in Earth Science, 2016)
A 51-year dataset (1961 to 2011) from nine meteorological stations in the capitals of northeastern Brazil (NEB), with daily data of precipitation totals and of mean, minimum and maximum temperatures, was statistically analyzed for data homogeneity and for signals of climate variability. The hypothesis was explored that a connection exists between inhomogeneities of the time series and the meteorological systems influencing the region. Results of the homogeneity analysis depend on the selected test variable, the test algorithm and the chosen significance level; all more or less subjective choices. Most of the temperature series was classified as “suspect”, while most of the precipitation series was categorized as “useful”. Displaying and visually checking the time series demonstrates the power of expertise and may allow for a deeper data analysis. Consistent changes in the seasonality of temperature and precipitation emerge over NEB despite manifold breaks in the temperature series. Both series appear to be coupled. The intra-annual temperature and precipitation ranges have increased, along with an intensified seasonal cycle. Temperature mainly increased during DJF, MAM and SON, with decreases in JJA being related to wetter conditions and more frequent heavy precipitation events. Drought conditions mostly increased in SON and DJF, depending on the timing of the local dry season.